Simple "in-water" vertical jump testing in water polo - Platanou, T. (Kinesiology, 2006)
The purpose of the present study was to develop a specific field test to assess accurately and reliably the ability of water polo players to perform a vertical jump in the water (in-water jump). Seventeen water polo players, competing in the Greek premier league, were tested at the vertical jump in the water and were measured in two ways; the first was in a laboratory with a 2-dimensional kinematic analysis (2D) and the other with a specific field test. The participants performed 3 trials for each procedure. The results for the field test were: for the first trial 67.6±6.0 cm, for the second 67.5 ±5.7 cm and for the third 67.4±5.6 cm. The mean value (68.6 ± 5.4 cm), with a range of 56.5 - 79.5 cm of the in-water jump, was assessed from the three best in-water trials. On the other hand, the mean value assessed on water for the vertical jump with the 2D kinematic technique was 65.3±5.9 cm. The results for the ANOVA with repeated measures showed no statistically signicant difference between the three trials of the field test (p<0.05) and the best performance as measured with the 2D technique. The interclass correlation coefficient was found to range between 0.92 and 0.98 between the 3 vertical jumps of the field test, whereas the correlation between the evaluation of the best vertical jump from the field test and the best vertical jump assessed by the 2D video recording was 0.96. The reliability of the measurement was established with the method of Bland and Altman. The results indicate that the specific field test of the vertical in-water jump is a reliable method to assess the ability for the vertical jump in the water.